2020
DOI: 10.1002/advs.202002697
|View full text |Cite
|
Sign up to set email alerts
|

2D Materials and Heterostructures at Extreme Pressure

Abstract: 2D materials possess wide-tuning properties ranging from semiconducting and metallization to superconducting, etc., which are determined by their structure, empowering them to be appealing in optoelectronic and photovoltaic applications. Pressure is an effective and clean tool that allows modifications of the electronic structure, crystal structure, morphologies, and compositions of 2D materials through van der Waals (vdW) interaction engineering. This enables an insightful understanding of the variable vdW in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(49 citation statements)
references
References 258 publications
(500 reference statements)
0
48
0
Order By: Relevance
“…Strain engineering is an important structural engineering technique used to tailor the optoelectronic properties in 2D materials for device fabrication. [ 199–203 ] For example, local strain engineering techniques are used to increase the carrier mobility in 2D material based FETs and tune the radiative wavelengths in nano photon emitters. [ 200–202,204–208 ] Accurate determination of strain vector is vital for the optimization of device performance.…”
Section: Characterization Of 2d Materials Using Optical Harmonic Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…Strain engineering is an important structural engineering technique used to tailor the optoelectronic properties in 2D materials for device fabrication. [ 199–203 ] For example, local strain engineering techniques are used to increase the carrier mobility in 2D material based FETs and tune the radiative wavelengths in nano photon emitters. [ 200–202,204–208 ] Accurate determination of strain vector is vital for the optimization of device performance.…”
Section: Characterization Of 2d Materials Using Optical Harmonic Generationmentioning
confidence: 99%
“…2D atomic crystals provide a testing ground to study strain engineering [ 195,282,283 ] and pressure variation [ 203,284,285 ] effects because they can resist high strain in the order of 10%. Furthermore, TMDs can be wrapped and folded.…”
Section: Tuning Of Optical Harmonic Generation In 2d Layered Materialsmentioning
confidence: 99%
“…This has prompted a burgeoning interest in high-pressure studies of 2D materials and a plethora of works that have demonstrated the potential of pressure for controlling a wide range of physical properties including lattice distortions and phase transitions, phonon dynamics, metallic or superconducting states, charge transfer and doping, and optical emission. 12 The modulation of the bandgap using hydrostatic pressure is a powerful probe into the strong coupling between mechanical and optical properties of layered materials. 13 A remarkable bandgap opening of 2.5 eV has been recently achieved in a semiconducting state of compressed trilayer graphene by tuning the interlayer hybridization.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12] To build various 2D/2D heterostructures, different 2D basic building blocks are required, which can be usually obtained via exfoliation or chemical growth method. [13][14][15][16][17][18][19][20] As illustrated in Figure 1d, there are some frequently applied 2D building blocks for 2D/2D heterostructures. Owing to its exceptional physical and chemical properties, conductive graphene is most widely unitized as an essential component of constructing various 2D/2D heterostructures, [21,22] such as graphene/hexagonal boron nitride (h-BN), [23] graphene/metal oxides (MOs), [24][25][26][27] graphene/transition metal dichalcogenides (TMDs), [28][29][30][31][32][33][34][35] graphene/layered double hydroxides (LDHs), [36,37] graphene/MXene, [38][39][40][41][42] graphene/black phosphorus (BP), [43,44] graphene/borophene [45] graphene/GaN heterostructures, etc.…”
Section: Introductionmentioning
confidence: 99%